2018
DOI: 10.1098/rsos.180613
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of reduced graphene oxide into faceted flower-like {001} TiO 2 for enhanced photocatalytic activity

Abstract: Anatase TiO2 with {001} facets is much more active than that with {101} facets, which has been verified via experiments and theoretical calculations. Graphene has garnered much attention since it was initially synthesized, due to its unique properties. In this study, reduced graphene oxide (RGO)/{001} faceted TiO2 composites were fabricated via a solvothermal method. The composites were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, X-ray photoelectron spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, Figure 2a-d shows the transmission electron microscopy images of rGO. From Figure 2a, it is observed that rGO is a transparent thin sheet-layered structure, which is prepared from graphene oxide [17]. Figure 2b shows the selected area electron diffraction (SAED) pattern of the rGO, which has two rings.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Figure 2a-d shows the transmission electron microscopy images of rGO. From Figure 2a, it is observed that rGO is a transparent thin sheet-layered structure, which is prepared from graphene oxide [17]. Figure 2b shows the selected area electron diffraction (SAED) pattern of the rGO, which has two rings.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al incorporated rGO into 001 faceted flower-like TiO 2 via solvothermal method. The results indicated that the photocatalytic activities of these composites were significantly improved following the incorporation of RGO, particularly under visible light irradiation [136]. Thien et al fabricated TiO 2 with highly exposed {001} facets decorated on reduced graphene oxide (RGO) sheets by simple solvothermal route.…”
Section: Applications 41 Tio 2 -001-based Composites For Photocatalytic Applicationsmentioning
confidence: 99%